2005
DOI: 10.1007/s11661-005-0146-8
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterizations of new glassy Co71Ti24B5 alloy powders and subsequent hot pressing into a fully dense bulk glass

Abstract: A single glassy phase of Co 71 Ti 24 B 5 alloy has been synthesized by high-energy ball milling the elemental powders at room temperature, using the mechanical alloying method. The synthetic glassy powder obtained after 130 ks of ball milling exhibits good soft magnetic properties with a polarization magnetization and coercivity values of 1.01 T and 2.86 kA/m, respectively. This ternary glassy alloy in which its glass transition temperature (T g ) lies at a rather high temperature (805 K) crystallizes at 868 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…However, the decrease in Ms after 1.5 h of milling could be due to the transformation of the crystalline phases to amorphous phases. Towards the end of the milling process, the Ms remained nearly constant because of the completion of the mechanically induced solid-state reaction [4,22,24]. As reported in Refs.…”
Section: Magnetic Propertiessupporting
confidence: 61%
See 2 more Smart Citations
“…However, the decrease in Ms after 1.5 h of milling could be due to the transformation of the crystalline phases to amorphous phases. Towards the end of the milling process, the Ms remained nearly constant because of the completion of the mechanically induced solid-state reaction [4,22,24]. As reported in Refs.…”
Section: Magnetic Propertiessupporting
confidence: 61%
“…El-Eskandarany et al [3] reported that a single amorphous phase of Co 75 Ti 25 alloy powders was obtained after a short MA time (11 ks). They also reported the formation of a single glassy phase of Co 71 Ti 24 B 5 alloy powders after 130 ks of milling [4]. Wu et al [5,6] developed the ferromagnetic Co-based amorphous alloys by replacing some of the Co with (Fe, Nb) or (Zr, Ti) elements, and found that the substitution reduces the thermal stability of the amorphous powders.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanical strength is lower than that (the compressive strength) of Fe-or (Fe, Co)-based bulk amorphous alloys, it is larger than that of large amorphous alloys prepared by the consolidation method. [11] The inset of Figure 5 shows the fracture surface of the sample. Crack is observed to propagate along the boundaries of the amorphous grains, but fracture occurs in the amorphous grain as well since there are vein patterns at the fracture surface.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…[1][2][3][4][5] Among other devices, MA is routinely carried out in planetary ball mills. The process involves high strain rate plastic deformation of a given powder charge within a confined volume that induces concomitant deformation, cold welding, fragmentation, interdiffusion, and dynamic recrystallization.…”
Section: Introductionmentioning
confidence: 99%